2013
DOI: 10.1002/jso.23373
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymphs nodes and lymph node ratio as predictive factors of survival in perforated and non-perforated T4 colorectal tumors

Abstract: In our experience, perforated cancers had higher survival rates and metastasis-free interval that non-perforated cancers, probably by a lower number of metastatic lymph nodes, smaller LNR and better TNM stage. Moreover the predictive value, in mortality rate, of metastatic lymph nodes and LNR was similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…This may lead to that these last tumors show an increase in vascular invasion ( P = 0.01) (Table 3 ) and a greater number of metastatic lymph nodes (Z = −4.2, P < 0.01) and LNR (Z = −4.03, P < 0.01) (Table 3 ), which will eventually lead to worse survival, as reported previously by our group. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to that these last tumors show an increase in vascular invasion ( P = 0.01) (Table 3 ) and a greater number of metastatic lymph nodes (Z = −4.2, P < 0.01) and LNR (Z = −4.03, P < 0.01) (Table 3 ), which will eventually lead to worse survival, as reported previously by our group. 5 …”
Section: Discussionmentioning
confidence: 99%
“… 1 4 Although perforation is generally associated with a poor prognosis and high mortality rates, it has been suggested that this poor outcome is limited to cases with immediate postoperative complications of sepsis. Our group recently reported 5 that patients with perforated colorectal tumors show better survival, related to better nodal stage, than patients with tumors that also reach the serosa but are not perforated. However, we know little about the pathophysiological factors or mechanisms underlying tumor invasion of the serosa ending with perforation in the abdominal cavity.…”
Section: Introductionmentioning
confidence: 97%
“…The status of lymph nodes often represents the degree of tumor progression . For most solid tumors, such as breast and pancreatic cancer, metastatic lymph nodes are determinant predictors of recurrence and poor survival .…”
Section: Introductionmentioning
confidence: 99%